Syntactic vs. phonological areas: A quantitative perspective on Hessian dialects. Issue 2 (3rd October 2021) - Birkenes, Magnus Breder; Fleischer, Jürg
Abstract: This paper takes a quantitative perspective on data from the project Syntax hessischer Dialekte (SyHD), covering dialects in the German state of Hesse, an area with rich dialectal variation. Many previous dialectometric analyses abstracted away from intralocal variation (e.g., by only counting the most frequent variant at a location). In contrast, we do justice to intralocal variation by taking into account local frequency relations. The study shows that the border between Low German and Central German—one of the most important isoglosses in German dialectology—is not relevant for syntactic phenomena. At the same time, a comparison with character n -grams (a global measure of string similarity) reveals that the traditionally assumed dialect areas, primarily defined according to phonological developments, are still present in the twenty-first century data. Different from previous studies, our results are obtained from a uniform data base. Therefore, the differences between syntax and phonology cannot be due to variation in sampling, elicitation method, or time of elicitation.